(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
To assess the effectiveness of surgical and medical interventions for urinary incontinence and/or pelvic organ prolapse, psychometric questionnaires are important to assess the quality of change in women’s lives. Although long forms of questionnaires are useful for research, short forms may be more widely used in clinical and practice research where it is important to minimize patient burden as well as reduce cost. We present a validated and reliable short form PISQ-12 questionnaire for the assessment of pelvic organ prolapse/urinary incontinence that accurately predicts and scores the problem.